汉语词语“一切”、“所有”、“全部”、“整个”与印尼文词语“semua”、“seluruh”、“segala”、“segenap”、“sekalian” 的词义与语用的对比分析 - Stephen Aji Wardana (Asosiasi Program Studi Mandarin Indonesia, 2019)
为了找出汉语词语“一切”、“所有”、“全部”、“整个”与印尼文词语“semua”、“seluruh”、“segala”、“segenap”、“sekalian”的异同、语义以及语用，本文使用对比分析假说的方式，提供每个词语的语义和语用，提出例句和病句，最后进行对比分析。研究结果证明了每个词语虽是同样是表示事物的总括，也表示事物的不明确数量，但在强调事物和种类方面就不同；汉语词语与印尼语词语的互换使用规律有两点。一，句子成分的位置必须一致。二，得注意每个词语的语义和使用的限制。在翻译工作的过程中，可以使用翻译手法的灵活性。只要句子的大意没有太大的变化或者还接近原句就没有问题。关键词：对比，分析，近义词，印尼词语，汉语词语 In order to discover the differences in semantic and pragmatic aspects of Chinese words “一切”、“所有”、“全部”、“整个” and Indonesian words “semua”、“seluruh”、“segala”、“segenap”、“sekalian”, this paper uses contrastive analysis hypothesis method. The research conducted by provides each word’s semantic and pragmatic description, giving out sentence samples and wrong sentences containing each words and then compares and analyses each sentences given. The research result shows some results: First, even though each words are both are indicates objects’ sum and also indicating unknown numbers, but there are differences between them such as which objects and what kind(s) of objects receives emphasizes. Second, is the rule of words exchanges: one, the specific role of words which need to be exchanged must be the same; two, the sentence’s context-limit must be in check before exchanges take places. In the translating process, we may considering the flexibility in translating method. As long as the main idea of the sentence does not undergo too many changes or still close to the original main idea. Keyword: comparison, analyze, close-meaning words, Indonesian words, Chinese words